The Impact of Maternal Position in Labor on Occiput-posterior Position of Fetus and Pregnancy Outcomes in Pregnant Women Without Epidural Analgesia - Hadis Bahmaei; Parvaneh Mousavi; Mohammad Hosein Haghighizadeh; Mina Iravani (Tehran University of Medical Sciences, 2023)
Objective: Fetal occiput posterior (OP) position is associated with more maternal and neonatal complications. This study aimed to investigate the effect of maternal position during labor on fetal OP position and pregnancy outcomes. Materials and methods: This randomized clinical trial study included 180 primigravida women in labor with a single fetus and approved OP position. Participants were randomly allocated into three groups: semi-prone position (n=45), knee-chest position (n=45), and supine position (n=90). All participants were placed in the defined positions 15-30 min in labor until delivery. Data collected using Visual Analogue Scale and researcher made checklist. The ANOVA, Tukey post hoc, and the chi-square test were used to analyze. Results: Among all participants who had OP, after intervention 16.3% in the semi-prone position, 14/3 % in the knee-chest position, and 33.7% of the control groups remained with OP at birth (X3=7/87, P=0.019). The rate of natural delivery was significantly higher in the semi-prone position and knee-chest position. The duration of active phase of labor and low back pain were significantly reduced in the semi-prone and knee-chest position compared to the control groups (P<0.05). There were no differences in the duration of the third stage of labor, APGAR score, and the rate of neonatal addition to neonatal intensive care unit, using oxytocin, and perineal tears (P>0.05). Conclusion: The semi-prone and knee-chest positions increase the spontaneous rotation of occiput to the anterior position, vaginal delivery rates as well as a reduction in duration of active phase of labor and low back pain after delivery.